Effectiveness of Electronic Traffic Law Enforcement in Enforcing Traffic Rules - Aldizar, Kendidan; Umam, Khoerul; Nursahidin; Sutarjo , Moh. (Riviera Publishing, 2025)
Technological developments have driven changes in the implementation of activities in various sectors, including government. Cirebon Regency also utilizes technological advances by implementing a mobile-based Electronic Traffic Law Enforcement (ETLE) system to reduce the number of traffic violations and accidents. The implementation of ETLE in Cirebon Regency is still not optimal, because public awareness to comply with traffic rules is still low, especially when there is no physical presence of officers on the road. This study uses a descriptive qualitative approach to measure the effectiveness of ETLE, obstacles in implementation, and efforts to overcome these obstacles. The results showed that the implementation of the ETLE system in Cirebon Regency has not fully run optimally. Some of the obstacles faced are the culture of people who are not orderly in traffic, limited equipment, and issues with the distribution and validation of violator data. The Cirebon Police Traffic Unit's efforts are needed to overcome these obstacles, such as conducting more evenly distributed socialization, procuring more adequate equipment, and developing face recognition technology to identify violators.